Implementation of Web GIS in Visualizing Certified Pharmacies Mapping by DPM PTSP in Kisaran Area - Aprianto, Muhammad Sura; Sembiring, Muhammad Ardiansyah; Marpaung, Nasrun (SAINTIS Publishing, 2025)
The advancement of information technology has enabled the utilization of Geographic Information Systems (GIS) in various fields, including healthcare services. This study aims to implement Web GIS for visualizing the mapping of certified pharmacies in the Kisaran area to provide easy access to information for the public and relevant stakeholders. The system is developed using web-based technology with PHP and MySQL to manage spatial data and pharmacy attributes. The results show that the developed Web GIS system can display location information, certification status, and pharmacy details interactively through a digital map. With this system, the public can easily identify certified pharmacies, thereby enhancing the safety and quality of healthcare services. Additionally, the implementation of this Web GIS assists the Investment and One-Stop Integrated Service Agency (DPM PTSP) in monitoring and managing pharmacy data more efficiently and transparently. The system also features a user-friendly interface that supports search and filter functionalities to improve user interaction. Data presented in real-time further improves the reliability of information accessed by users. Furthermore, this Web GIS solution contributes to spatial-based decision making, enabling authorities to conduct targeted inspections, identify underserved areas, and plan the development of new pharmacies based on geographic distribution. The integration of spatial data with pharmacy certification records also supports transparency and accountability in public health service management. In conclusion, this research demonstrates the potential of Web GIS as an effective tool for improving access to reliable health service information and enhancing the operational performance of relevant governmental institutions.